2015
DOI: 10.3390/jmse3030539
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Crab Burrows Facilitate Desalting of Rooted Mangrove Sediment in a Microcosm Study

Abstract: Water uptake by mangrove trees can result in salt accumulation in sediment around roots, negatively influencing growth. Tidal pumping facilitates salt release and can be enhanced by crab burrows. Similarly, flushing of burrows by incoming tidal water decreases sediment salinity. In contrast to burrows with multiple entrances, the role of burrows with one opening for salinity reduction is largely unknown. In a microcosm experiment we studied the effect of artificial, burrow-like macro-pores with one opening on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
1
13
1
Order By: Relevance
“…This refutes our hypothesis of lower sediment salinity at areas with higher density of crab burrows during this time of year. The result corroborates the findings of Pülmanns et al (2015) in the rainy season, when sediment salinity in "rooted" areas was also higher than in "gap" areas (27 and 31 in gap areas and rooted areas, respectively, at the end of the rainy season) Findings by Smith III (1987), demonstrating a salinity of 57.5 in areas with high amounts of aerial roots versus 55.2 in gaps, are also in concordance with the present results. A microcosm experiment by Pülmanns et al (2016), showed lower salinity in treatments with (41) than without (47) artificial burrows after 6 months (both treatments started with sediment salinity of 37.5 at the first centimeter),…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This refutes our hypothesis of lower sediment salinity at areas with higher density of crab burrows during this time of year. The result corroborates the findings of Pülmanns et al (2015) in the rainy season, when sediment salinity in "rooted" areas was also higher than in "gap" areas (27 and 31 in gap areas and rooted areas, respectively, at the end of the rainy season) Findings by Smith III (1987), demonstrating a salinity of 57.5 in areas with high amounts of aerial roots versus 55.2 in gaps, are also in concordance with the present results. A microcosm experiment by Pülmanns et al (2016), showed lower salinity in treatments with (41) than without (47) artificial burrows after 6 months (both treatments started with sediment salinity of 37.5 at the first centimeter),…”
Section: Discussionsupporting
confidence: 92%
“…The tides at the study area are semidiurnal with a range between 3 and 5 m. The forest at the study site is located in the high intertidal zone which is not flooded during neap high tides (Pülmanns et al, 2015). The region has two very distinct seasons.…”
Section: Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, small-scale topographical variations (±15 cm) have been shown to influence pneumatophore abundance and length [15]. Macropores, or cavities in soils, increase drainage of water and help facilitate transport of solutions, salt, and other particles in sediments [16,17]. These macropores are usually created by penetration by plant roots, burrowing activities by soil invertebrates, and aggregation of soil particles [18][19][20].…”
Section: Introductionmentioning
confidence: 99%